2016
DOI: 10.1002/pbc.26155
|View full text |Cite
|
Sign up to set email alerts
|

Otologic manifestations of Fanconi anemia and other inherited bone marrow failure syndromes

Abstract: FA is the major IBMFS with associated hearing loss, which is most commonly conductive. Radial hypoplasia or aplasia and characteristic congenital ear malformations are associated with hearing loss in patients with FA. Recognition of these syndrome-specific abnormalities should lead to earlier management of hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Therefore, mild hearing loss, present in 62.5% of our FA patients with hearing loss, could easily have been missed. Two other studies reported a hearing loss prevalence of 50% and 45%, which is in line with our results . As in our population, in literature, the described hearing loss in FA is mostly conductive However, we found higher prevalences of sensorineural and mixed hearing loss compared to other studies .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, mild hearing loss, present in 62.5% of our FA patients with hearing loss, could easily have been missed. Two other studies reported a hearing loss prevalence of 50% and 45%, which is in line with our results . As in our population, in literature, the described hearing loss in FA is mostly conductive However, we found higher prevalences of sensorineural and mixed hearing loss compared to other studies .…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of otological problems in patients with FA varies from 10% to 20% according to literature reviews ( 1 , 2 ). Hearing impairments are more frequent in FA compared with other IBMFS ( 177 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 91%
“…Structural ear anomalies of any kind have been found in more than half of patients after an intentional evaluation ( 177 ). As it appears to be the rule in FA, the structural abnormality range is wide.…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 99%
See 2 more Smart Citations